Cascading effects of a disease outbreak in a remote protected area. (17th February 2022) - Monk, Julia D.; Smith, Justine A.; Donadío, Emiliano; Perrig, Paula L.; Crego, Ramiro D.; Fileni, Martin; Bidder, Owen; Lambertucci, Sergio A.; Pauli, Jonathan N.; Schmitz, Oswald J.; Middleton, Arthur D.
Abstract: Disease outbreaks induced by humans increasingly threaten wildlife communities worldwide. Like predators, pathogens can be key top‐down forces in ecosystems, initiating trophic cascades that may alter food webs. An outbreak of mange in a remote Andean protected area caused a dramatic population decline in a mammalian herbivore (the vicuña), creating conditions to test the cascading effects of disease on the ecological community. By comparing a suite of ecological measurements to pre‐disease baseline records, we demonstrate that mange restructured tightly linked trophic interactions previously driven by a mammalian predator (the puma). Following the mange outbreak, scavenger (Andean condor) occurrence in the ecosystem declined sharply and plant biomass and cover increased dramatically in predation refuges where herbivory was historically concentrated. The evidence shows that a disease‐induced trophic cascade, mediated by vicuña density, could supplant the predator‐induced trophic cascade, mediated by vicuña behaviour, thereby transforming the Andean ecosystem. Abstract : An outbreak of Sarcoptic mange in a vicuña population in a remote protected area in the Argentine Andes reconfigured the tightly‐linked vertebrate food web, transforming a trophic cascade. Mange triggered a population crash in the large mammalian herbivore that released vegetation in predation refuge habitats, but not in habitats with high predation risk, where a behaviourally mediated trophic cascade driven by puma predation shielded vegetation from the effects of herbivory. This disease‐mediated shift also led to the near‐abandonment of the protected area by the dominant scavenger, the Andean condor, which was previously tethered to the region by a steady provisioning of vicuña carcasses from puma predation.